2007
DOI: 10.1042/bj20070687
|View full text |Cite
|
Sign up to set email alerts
|

Lactate favours the dissociation of skeletal muscle 6-phosphofructo-1-kinase tetramers down-regulating the enzyme and muscle glycolysis

Abstract: For a long period lactate was considered as a dead-end product of glycolysis in many cells and its accumulation correlated with acidosis and cellular and tissue damage. At present, the role of lactate in several physiological processes has been investigated based on its properties as an energy source, a signalling molecule and as essential for tissue repair. It is noteworthy that lactate accumulation alters glycolytic flux independently from medium acidification, thereby this compound can regulate glucose meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(66 citation statements)
references
References 41 publications
(93 reference statements)
3
63
0
Order By: Relevance
“…It is known that lactate inhibits PFK-1, a key regulatory enzyme of glycolysis, and favors the dissociation of active PFK-1 tetramers into less active dimers (42). In the light of our findings, intracellular lactate accumulation could suppress PFK-1 and thereby reduce the glycolytic flux in monocytes.…”
Section: Discussionmentioning
confidence: 73%
“…It is known that lactate inhibits PFK-1, a key regulatory enzyme of glycolysis, and favors the dissociation of active PFK-1 tetramers into less active dimers (42). In the light of our findings, intracellular lactate accumulation could suppress PFK-1 and thereby reduce the glycolytic flux in monocytes.…”
Section: Discussionmentioning
confidence: 73%
“…In those cases, the high levels of lactate accumulated in culture causes inhibition of PFK [54], [55] and induces a shift in the metabolism to lactate consumption (Mulukutla et al, in preparation). The extended model includes the pentose phosphate pathway (PPP) and the TCA cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle phosphofructokinase can be phosphorylated at several sites by several protein kinases, which are dependent on what hormones (insulin, epinephrine, or others) are regulating the phosphorylation [44]. Phosphorylation decreases the inhibitory effect of ATP or lactate on phosphofructokinase by stabilizing the tetrameric form of the enzyme [45,46]. Indeed, many studies have shown an increase in circulating insulin in response to heat stress when compared to pair fed counterparts [11,12].…”
Section: Glycolysismentioning
confidence: 96%